Стратегічне управління конкурентоспроможністю підприємства на засадах контролінгу - Лопатинський, Юрій (My University, 2023)
У статті розглянуто основні теоретичні положення стратегічного управління конкурентоспроможністю підприємств на основі використання технології контролінгу. Узагальнено основні напрямки стратегії підвищення конкурентоспроможності підприємств на сучасному етапі розвитку економічних процесів. Зазначено, що на основі дослідження основних ендо- та екзофакторів підприємство здатне розробити ефективну стратегію, що спрямована на підвищення конкурентоспроможності на основі мінімізації негативного впливу окремих чинників та максимізації впливу позитивних факторів. Сформовано систему стратегій управління конкурентоспроможністю, що в подальшому може слугувати орієнтиром майбутньої діяльності підприємства залежно від рівня його конкурентоспроможності в цілому та окремих її елементів. Обґрунтовано, що сучасна концепція управління конкурентоспроможністю має ґрунтуватись на використанні дієвих сучасних управлінських інструментів, а саме контролінгу. Зазначено, що в контексті реалізації стратегічного управління конкурентоспроможністю підприємства система контролінгу являє собою нову концепцію інформатизації управління на основі формування обліково-аналітичної системи та синтезу елементів обліку, планування, аналізу, моніторингу. Визначено функціональну складову контролінгу в системі управління конкурентоспроможністю підприємства, систематизовано характеристики оперативного та стратегічного контролінгу. Виокремлено пріоритетні завдання контролінгу в контексті підвищення рівня конкурентоспроможності та підсилення ринкової позиції підприємства. Сформовано систему принципів реалізації контролінгу як інструменту управління конкурентоспроможністю та визначено послідовність реалізації функцій стратегічного управління на засадах контролінгу.
STRATEGIC MANAGEMENT OF ENTERPRISE COMPETITIVENESS BASED ON CONTROLLING PRINCIPLES
The article discusses the main theoretical principles of strategic management for enterprise competitiveness based on the utilization of controlling technology. The article's objective is to develop the conceptual foundations of strategic management for enterprise competitiveness through controlling. The general directions of the strategy to enhance the competitiveness of enterprises in the current stage of economic processes development have been summarized. It has been noted that by studying the main endo- and exofactors, a company can develop an effective strategy aimed at increasing competitiveness by minimizing the negative impact of individual factors and maximizing the influence of positive factors. A system of competitiveness management strategies has been established, which can serve as a guide for the future activities of the enterprise, depending on its overall competitiveness level and individual elements. It is argued that the modern concept of competitiveness management should be grounded in the use of effective modern management tools, specifically controlling. It is highlighted that, in the context of implementing strategic management of enterprise competitiveness, the controlling system represents a new concept of management informatization. This system is based on the formation of an accounting and analytical system and the synthesis of elements of planning, analysis, and monitoring. The functional component of controlling in the enterprise competitiveness management system has been defined, and the characteristics of operational and strategic controlling have been systematized. The priority tasks of controlling in the context of increasing the level of competitiveness and strengthening the market position of the enterprise have been emphasized. It is substantiated that the introduction of controlling into the competitiveness management system is based on the function of strategic planning, with the key aspect being the development and subsequent implementation of the competitiveness strategy. A system of principles for the implementation of controlling as a competitive management tool has been formulated, and the sequence of implementing strategic management functions based on controlling has been determined.
Keywords: контролінг; конкурентоспроможність; стратегічне управління; стратегія; система управління конкурентоспроможністю; controlling; competitiveness; strategic management; strategy; competitiveness management system